Uterine Cancer Diagnosis and Treatment - Rajaram, Shalini.; Rajaram, Shalini.; K, Chitrathara.; K, Chitrathara.; Maheshwari, Amita.; Maheshwari, Amita. (Springer India : Imprint: Springer, 2015)
Uterine cancers are the commonest malignancies of the female genital tract in the developed world, and are increasing in numbers world over because of obesity and other life-style changes. Many of these malignancies are hereditary and thus, a better understanding of the genetic and molecular biology is needed. This would lead to appropriate treatment plan for improving the quality of life and long-term survival. This book addresses, in depth, all aspects of uterine malignancies covering both carcinomas and sarcomas. The book is divided into seven sections; the first two sections deal with epidemiology, molecular aspects, familial cancers and pathology and the later sections focus on diagnosis, imaging techniques and comprehensive management of both early stage and advanced cancers. Surgical techniques, adjuvant chemotherapy and radiotherapy have been covered in detail. Apart from the open surgical methods, role of laparoscopy and emerging role of robotic surgery in the contemporary management of endometrial cancers have been discussed. Written by authors with expertise in the field of gynecologic oncology from premier institutes, this book provides up-to-date information on best practice management of uterine malignancies.